Examination of the Effective Utilization of the CARELINK® Remote Monitoring System after its Introduction - Miyamoto, Satoshi; Nakano, Yukiko, MD; Okahara, Shigeyuki; Takahashi, Hidenobu; Matsuzaki, Hisayasu; Oda, Noboru, MD; Imai, Katsuhiko, MD; Sueda, Taijirou, MD; Kihara, Yasuki, MD (Journal of Arrhythmia, 2011)
Abstract Background: Japan started using the CARELINK® (Medtronic, Inc, Minneapolis, MN, USA) remote monitoring system in April 2009. However, in some cases, the device failed to transmit a message after registration or according to schedule. We investigated the difference between patients who could make effective use of CARELINK® system and those who could not. Subjects and Method: Sixty patients who had registered until December 2009 at our institution were analyzed. These patients were divided into two groups: those who were able to use the device effectively (group G, n = 49) and those who were not (group F = 11). Patient background, automatic or manual telemetries, new or existing implant patient, presence of adverse events, and the use or non-use of a checklist at the time of introduction were compared between the two groups. Results: In group G, more patients used a checklist at the time of introduction than that in group F (use of checklist/total, 31/49 in group G vs. 3/11 in group F; P, 0.029). No significant difference was observed in other factors between the two groups. Conclusion: We consider that the method used to explain the system are important to make the patients understand handling methods of CARELINK® system. The number of patients introduced to remote monitoring of implantable devices will continue to increase in the future; therefore, we must continue to develop innovative approaches for their effective us.